2004
DOI: 10.1111/j.1444-2906.2004.00871.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of sodium bicarbonate on the initiation of sperm motility in the Japanese eel

Abstract: In order to find out the role of sodium bicarbonate (NaHCO 3 ) on the initiation of sperm motility in the Japanese eel Anguilla japonica , interactions were investigated between NaHCO 3 and various reagents (K + channel blocker 4-aminopyridine [4-AP], ammonium chloride [NH 4 Cl], sodium acetate and calcium chloride [CaCl 2 ]) that could regulate internal factors (intracellular K + , intracellular pH [[pH] i ] and intracellular Ca 2 + ) in sperm motility. Contradictory effects of NaHCO 3 were observed (i.e. an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 26 publications
(80 reference statements)
1
21
0
Order By: Relevance
“…This decrease should be considered in order to find ways of improvement of the techniques for the cryopreservation of European eel sperm. The way to improve the protocols should consider several aspects as dilution factors (sperm : freezing medium), addition of compounds with friendly effect with the spermatozoa membrane as L‐ α ‐phosphatidylcholine, and variations on the ionic composition of freezing media taken into account for instance the sodium bicarbonate concentrations that could be a critical point due its role controlling the initiation of spermatozoa motility as has been probed in the Japanese eel (Tanaka et al. 2002a,b, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…This decrease should be considered in order to find ways of improvement of the techniques for the cryopreservation of European eel sperm. The way to improve the protocols should consider several aspects as dilution factors (sperm : freezing medium), addition of compounds with friendly effect with the spermatozoa membrane as L‐ α ‐phosphatidylcholine, and variations on the ionic composition of freezing media taken into account for instance the sodium bicarbonate concentrations that could be a critical point due its role controlling the initiation of spermatozoa motility as has been probed in the Japanese eel (Tanaka et al. 2002a,b, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…(2002a); Tanaka, Zhang, Yamada, Okamura, Horie, Utoh, Mikawa, Oka and Kurokura (2002b) suggested that NaHCO 3 has an inhibitory role in the Japanese eel spermatozoa motility, as a consequence of its dissociation in some products, which may influence intracellular pH. Two years later, Tanaka, Utoh, Yamada, Horie, Okamura, Akazawa, Mikawa, Oka and Kurokura (2004) suggested that NaHCO 3 has a dual role in the control of spermatozoa motility depending on its dissociation products: one inhibiting role mediated by CO 2 and one activating role mediated by HCO 3 − .…”
Section: Discussionmentioning
confidence: 99%
“…In the same study it was shown that pH also regulated sperm motility in puffer fish; in demembranated sperm motility was initiated at a high pH, and terminated at a low pH (Takai & Morisawa, 1995). In the Atlantic croaker (Micropogonias undulatus) and the Japanese eel (Anguilla japonica), the K + channel inhibitor 4-AP inhibited sperm motility (Detweiler & Thomas, 1997;Tanaka et al 2004). In the Japanese eel the inhibitory effect of 4-AP disappeared when the pH i was decreased using Na-acetate, when CO 2 or NaHCO 3 was added, or when the pH from the activation media was lower than 8.2 (Tanaka et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…In the Atlantic croaker (Micropogonias undulatus) and the Japanese eel (Anguilla japonica), the K + channel inhibitor 4-AP inhibited sperm motility (Detweiler & Thomas, 1997;Tanaka et al 2004). In the Japanese eel the inhibitory effect of 4-AP disappeared when the pH i was decreased using Na-acetate, when CO 2 or NaHCO 3 was added, or when the pH from the activation media was lower than 8.2 (Tanaka et al, 2004). It was suggested that in the Japanese eel, an uptake of H + triggers the initiation of sperm motility with the participation of a K + transport through a K + channel sensitive to 4-AP.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation